Men in Early Childhood Education and Care Gender Balance and Flexibility - Warin, Jo (Palgrave Studies in Gender and Education,, 2018)
Palgrave Studies in Gender and Education Series Editor: Yvette Taylor, University of Strathclyde, UK This book examines the current interest in recruiting and supporting more men in the early childhood education workforce. Drawing on extensive empirical data from case studies of an unusual English preschool setting and interviews with Swedish male preschool staff, the author explores the potential benefits to society linked to the increased presence of men in early childhood education, and how this might be achieved. Throughout the book, the author maintains that the potential of including more men in early childhood education can only be achieved by gender-sensitive practitioners, both women and men, who are willing to create a gender-flexible pedagogy. This volume will be of interest and value to students, academics and practitioners interested in gender diversity and equity within early childhood education and care. Jo Warin is Senior Lecturer in the Department of Educational Research at Lancaster University, UK, and co-director of the Centre for Social Justice and Wellbeing in Education. She has researched extensively in the fields of gender, identity and education.